2014
DOI: 10.1063/1.4879055
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic ferromagnetism in hexagonal boron nitride nanosheets

Abstract: Understanding the mechanism of ferromagnetism in hexagonal boron nitride nanosheets, which possess only s and p electrons in comparison with normal ferromagnets based on localized d or f electrons, is a current challenge. In this work, we report an experimental finding that the ferromagnetic coupling is an intrinsic property of hexagonal boron nitride nanosheets, which has never been reported before. Moreover, we further confirm it from ab initio calculations. We show that the measured ferromagnetism should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
2
17
1
Order By: Relevance
“…6c and d). The weak hysteresis loops indicate weak FM behavior of both samples, which is close to the previous reports 3, 14 . Figure 3d shows that saturation magnetization ( M s ) of BCN nanosheets are 0.004, 0.068, and 0.134 emu/g (0.12 μ B /C); the corresponding coercive fields ( H C ) are 25, 61, and 81 Oe, respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…6c and d). The weak hysteresis loops indicate weak FM behavior of both samples, which is close to the previous reports 3, 14 . Figure 3d shows that saturation magnetization ( M s ) of BCN nanosheets are 0.004, 0.068, and 0.134 emu/g (0.12 μ B /C); the corresponding coercive fields ( H C ) are 25, 61, and 81 Oe, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Thus, band gap engineering and inducing stable ferromagnetism ( FM ) are equally important for BNNSs. Until now, FM has been achieved experimentally in BNNSs through defects 14 or dopants 15 control. However, to the best of our knowledge, there are no reports on the demonstration of controlling the band gap and optical properties of metal-free element doped BNNSs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vacancies in some other non-magnetic materials can also induce magnetism. Si et al [19] found that vacancies in hexagonal boron nitride nanosheets (h-BN) could generate magnetic moments and form ferromagnetism, and they conducted some experiments to test their discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetism which arises due to completely-filled or unfilled d-/f-orbitals is known as d • ferromagnetism and is a wide field of study for the scientific community from a phenomenological point of view [4][5][6][7][8]. To date, this magnetism is observed in a variety of materials with different sources of origin and is classified accordingly [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, materials with partially-filled d-/f-orbitals exhibit this phenomenon [1][2][3]. Apart from this, magnetic behavior of certain materials with completely-filled or zero-filled d-/f-shells is also observed and has remained under debate among researchers during the last decade [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%